Effectiveness of GABA agonist for treatment in mice with complete freuds adjuvants induced chronic pain: molecular modeling approach (International Current Pharmaceutical Journal, 2013)
The present study was designed to investigate the effectiveness of gaba agonist in behavioral changes of inflammatory mice with molecular docking approach. Forty mice were divided into 8 groups i.e. sham, gabapentin (10, 30 and 100 nmol), baclofen (1, 10 and 30 nmol) and negative control. Chronic pain was induced by inflammatory agent such as Complete Freuds Adjuvant (CFA). On day 8 after intraplantar injection of CFA, mice were treated by intrathecal with normal saline (sham and negative control groups), gabapentin and baclofen with three different doses, once a day for seven consecutive days. Latency time toward thermal stimulus was measured on days 1,2,8,9,11 and 15 after induction. The molecular docking was examined by Mollegro virtual docker program. The result showed that intrathecal injection of gabapentin and baclofen increased time latency toward thermal stimulus compared to negative control. There were differences between gabapentin and baclofen doses for chronic pain treatment. Molecular docking showed that the differences of effective dose were related to type of amino acid binding between gabapentin and baclofen.DOI: http://dx.doi.org/10.3329/icpj.v2i2.13194 International Current Pharmaceutical Journal 2013, 2(2): 29-32